The Alterations of Vaginal Microbiome in HPV16 Infection as Identified by Shotgun Metagenomic Sequencing - Yang, Qian; Wang, Yaping; Wei, Xinyi; Zhu, Jiawei; Wang, Xinyu; Xie, Xing; Lu, Weiguo (Frontiers in Cellular and Infection Microbiology, 2020)
The association of microbiome imbalance with cancer development is being one of the research hotspots. Persistent HPV infection is a causal event in cervical cancer initiation, but, little is known about the microbiome composition and function in HPV infection. Here we identified the compositional and functional alterations on vaginal samples from 27 HPV16 positive women and 25 age-matched HPV negative controls using shotgun metagenomic sequencing, to provide a comprehensive investigation describing the microbial abundances and enriched metabolic functions in cervicovaginal metagenomes. We further employed qPCR assays to evaluate two selected gene markers of HPV16 infection in an independent validation cohort consisting of 88 HPV16 positive women and 81 controls, and six selected species markers in a subset of validation cohort of 45 HPV16 positive women and 53 controls. We found that the relative abundance of dominant Firmicutes was lower, Actinobacteria, Fusobacteria and viruses phyla were significantly higher in the HPV16-positive group; 77 genera including Gardnerella, Peptostreptococcus, and Prevotella were higher, and 20 genera including Lactobacillus and Aerococcus were lower in the HPV16-positive women. Abundance of 12 genes, 17 genera, and 7 species biomarkers showed an excellent predictive power for the HPV16-positive individuals, with 0.861, 0.819, and 0.918, respectively, of the area under the receiver-operating characteristic curve (AUC). We further characterized the microbial function, and revealed that HPV16-positive women were enriched in metabolism and membrane transport, and depleted by glycan biosynthesis and metabolism, and replication and repair. Quantitative PCR measurements validated that one gene marker and three species were significantly enriched in HPV16-positive women. These results highlight a fundamental fact that there are altered composition and function of the vaginal microbiome in HPV16-positive women, suggesting that vaginal dysbiosis may be associated with HPV infection in the female genital tract.